2015
DOI: 10.1080/13501763.2015.1085073
|View full text |Cite
|
Sign up to set email alerts
|

The politics of global value chains: import-dependent firms and EU–Asia trade agreements

Abstract: In 2006, the European Commission released its Global Europe Communication, in which it announced a shift from a multilateral to a bilateral trade strategy. One of the key pillars of this new strategy was to strengthen the bilateral trade relations with key Asian countries. In contrast to existing analyses that focus on European Union (EU) decision makers’ agency, we propose an explanation for this notable shift in the EU’s trade policy that stresses the political role of import-dependent firms. In light of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
(40 reference statements)
2
51
0
Order By: Relevance
“…This changes the balance of domestic trade‐related interests by increasing the domestic coalition of firms favoring trade liberalization. While traditionally seen as a battle between firms exporting in foreign markets, that is, firms in export oriented sectors, and firms fearing competition from foreign producers, that is, firms in import‐competing sectors, GVCs make import‐dependent firms more important in the domestic political economy and thus stimulate support for PTAs (Eckhardt and Poletti, ; Manger, ). In addition, GVCs create incentives for greater regulatory harmonization, generating a demand for PTAs that are broader in scope (Baldwin, ).…”
Section: Institutions and Gvcsmentioning
confidence: 99%
“…This changes the balance of domestic trade‐related interests by increasing the domestic coalition of firms favoring trade liberalization. While traditionally seen as a battle between firms exporting in foreign markets, that is, firms in export oriented sectors, and firms fearing competition from foreign producers, that is, firms in import‐competing sectors, GVCs make import‐dependent firms more important in the domestic political economy and thus stimulate support for PTAs (Eckhardt and Poletti, ; Manger, ). In addition, GVCs create incentives for greater regulatory harmonization, generating a demand for PTAs that are broader in scope (Baldwin, ).…”
Section: Institutions and Gvcsmentioning
confidence: 99%
“…72 In similar vein, import-dependent firms have found to have played an important role in the recent decision by the EU to open PTA negotiations with some of its Asian trading partners. 73 We also see the influence of interest groups on trade remedy decisions. Import-competing firms, for instance, successfully blocked a recent attempt by the European Commission to reform its Trade Defense Instruments (TDI) policy, 74 while also in individual TDI cases we witness the influence of both import-competitors and import-dependent firms.…”
Section: Explaining Variation In Support Of International Trade Lawmentioning
confidence: 93%
“…Yet, the heterogeneity of firms within the same sector goes beyond variation in (export) performance: firms also differ in their ability to engage in transnational production activities and to establish (global and/or regional) value chains (Osgood, ). Scholars have found that firms’ preferences depend to a significant extend on their ability to source (intermediates) from – and open production facilities overseas, as well as their integration and position within (regional or global) value chains (Curran, ; Eckhardt, ; Eckhardt and Poletti, ; Kim, ; Manger, ; Osgood, ; Yildirim et al., ). That is, firms that heavily depend on foreign imports and production and/or are integrated in GVCs are most likely to have pro‐trade preferences.…”
Section: Business Interests and The Politics Of Tradementioning
confidence: 99%